Research work at the Bari Institute on the reuse of low quality water and its impact on soils and plants - Hamdy A. (Reuse of low quality water for irrigation, 1989)
The Bari Institute started a research programme on the use of saline water in irrigation including: the influence of irrigation with saline water of different salt concentration levels on the growth and yield of some main crops in the Mediterranean area; - the mode of saline water application; salt accumulation and its distribution in the different soil layers under saline water irrigation using different irrigation methods and leaching the accumulated excess salts using fresh water as well as water of low quality. This paper summarises the experimental work included in the programme and the results obtained by giving some outlines which could be utilised as far as we are concerned for establishing a new strategy for the use of low water quality in irrigation.
Aswan Seminar, 1988/01/16-21, Cairo (Egypt)